Improving Long Service Ability in Badminton Game Through Blocked Practice Method in Class V.1 Students of SDN 83 Kendari - Marwiah (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2023)
This study aims to improve long-service skills in badminton games through the blocked practice method in class V1 students of SD Negeri 83 Kendari. This study hypothesizes that the blocked practice method can improve long-service abilities in V.1 students. This research was conducted at SD Negeri 83 Kendari in September-October 2019. The subjects of this research were all students in class V.1 SD Negeri 83 Kendari, totaling 34 students, consisting of 18 female students and 16 male students. Data collection techniques include observation, tests, and documentation. This study used classroom action research, which consisted of two cycles, each consisting of 2 meetings. The results showed that the blocked practice method could improve long-service skills in V.1 students. This can be seen from the average score of the student's skills test results in cycle I, which was 73.8 points with a classical completeness of 56%, and in cycle II, the results of the skills test of students doing back rolls increased to 84.7 with a classical completeness of 84%.